Nilai-Nilai Pendidikan Karakter Dalam Budaya Masyarakat Bugis Bone - Sarifa Suhra (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
This article with regard to the educational values of characters in the tradition of the Bugis community and aims to determine the values of character education contained in (pappaseng) and (elong). Qualitative descriptive nature of this study, use several approaches sociological. Data consisted of primary and secondary. The primary data sourced from books containing (pappaseng) and other informants who support as: Bugis community leaders. The results showed that there is some educational value in (pappaseng) character as such as: caring, tolerance and democracy, honest, clean, and patience. characters patience in (elong) reads: (Ininnawa sabbarakki lolongeng gare Deceng tosabbaraede), (Pitu taunna sabbara tengnginang kulolongeng riyasengnge Deceng, Deceng enrekki ri bola tejjali tettappere banna mase-mase). The conclusion of the research in the Bugis community are knowen (pappaseng) and (elong)to be loaded with the value of character education.